Problems of realization of international legal assistance during the cooperation of Ukraine with foreign states - Khatuntsev, Vadym (Global Prosperity, 2022)
The article is devoted to the study of the problems of the implementation of international legal aid during Ukraine’s cooperation with foreign countries. It has been established that in the aspect of criminal proceedings, international legal assistance is understood as the conduct of procedural actions by the competent authorities of one state, the implementation of which is necessary for a pre-trial investigation, trial or for the execution of a sentence passed by a court of another state or an international judicial institution. It was found that during the cooperation of Ukraine with foreign countries, international legal assistance can be implemented by handing over documents, performing certain procedural actions, extradition of persons who have committed a criminal offense, temporary transfer of persons, taking over criminal prosecution, transfer of convicted persons and execution of sentences. At the same time, in the realities of wartime, the implementation of certain procedural actions as a form of international legal assistance is of the greatest importance, which is primarily due to the unprecedented scale of crimes committed by the russian federation in Ukraine and the need to identify a large number of war criminals and crimes, as well as bring the guilty parties to justice. Effective investigation of such crimes requires the use of considerable resources and the appropriate competence of investigators, experts, and prosecutors. Therefore, it is currently important to involve in this process international specialists and foreign experts who have experience in documenting and investigating war crimes, crimes against humanity, and the crime of genocide. At the same time, taking into account the scale of the destruction caused by the armed aggression of the Russian Federation, the economic, environmental, material, and moral damages, cooperation aimed at the search, arrest, and confiscation of assets of persons involved in war crimes committed on the territory of Ukraine is becoming more and more relevant. However, at the same time, other forms of international legal assistance do not lose their relevance. Taking into account the scale of the destruction caused by the armed aggression of the Russian Federation, economic, environmental, material, and moral damages, cooperation aimed at the search, arrest, and confiscation of assets of persons involved in war crimes committed on the territory of Ukraine is becoming more and more relevant. However, at the same time, other forms of international legal assistance do not lose their relevance. Taking into account the scale of the destruction caused by the armed aggression of the Russian federation, economic, environmental, material, and moral damages, cooperation aimed at the search, arrest, and confiscation of assets of persons involved in war crimes committed on the territory of Ukraine is becoming more and more relevant. However, at the same time, other forms of international legal assistance do not lose their relevance.